Study of the Use of Data Mining in Modeling Non-standard Processes in a Higher Education Institution - Maia, Diogo Rocha Ferreira; de Campos, Renato [UNESP]; de Souza Rodrigues, José [UNESP] (Springer Nature, 2020)
Business process management (BPM) is an administration discipline to design, improve and manage processes, and consists of several phases. One of them is the modeling of the current process (as is), during which the process is mapped as it is. One tool that can be used in the process discovery and modeling phase is data mining in information systems. Data mining techniques allow a series of applications in organizations, either as a verification process or as a discovery process. The purpose of this article is to analyze the use of data mining in the modeling stage of complex and not well structured processes when applying BPM to improve processes at a Federal Institute of Higher Education in Brazil. Due to the fact that the nature of the products and services requested in the institute’s system is very varied, the processes are not standardized, and the use of the information system is not done in a disciplined way, data mining was not enough to identify the complete processes and the flow of activities in detail. Although it was not enough, data mining facilitated the definition of instance flows and made it possible to detect critical points in the process, such as points with a long duration of time. With data mining, the analysis time, meetings and modeling effort of the analysts and users were reduced.
Keywords: BPM; Business process management; Data mining; Higher education; Non-standard processes